The overlap between viewing child sexual abuse material and fringe or radical content online - Cubitt, Timothy (Trends & issues in crime and criminal justice, 2024)
Drawing on a survey of 13,302 online Australians, this study examines the characteristics and behaviours of respondents who viewed child sexual abuse material (CSAM) and fringe or radical content online, or both. In the past 12 months, 40.6 percent of respondents had viewed fringe or radical content and 4.5 percent had viewed CSAM. Among respondents who viewed CSAM, 64.7 percent had also viewed fringe or radical content, while 7.1 percent of those who viewed radical content had also viewed CSAM. Respondents who viewed only CSAM or only fringe or radical content were similar to one another. Respondents who viewed both were more likely to be younger and male and had higher rates of criminal justice system contact and diagnosed mental illness. Their online activity, including the platforms used, also differed.